2013
DOI: 10.3390/pharmaceutics5040570
|View full text |Cite
|
Sign up to set email alerts
|

Design of Olanzapine/Lutrol Solid Dispersions of Improved Stability and Performances

Abstract: Eleven solid dispersions containing olanzapine, with carriers of different composition (Lutrol® F68, Lutrol® F127, Gelucire® 44/14), were prepared and examined by thermal (differential scanning calorimetry (DSC); thermomicroscopy (HSM)) and X-ray diffraction (XRD) analysis, both as fresh or aged (one year) samples. Drug and carriers were preliminarily selected in order to avoid problems related to the aging of the formulation, according to the solubility parameters of carriers and drug. These parameters make i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The PEO single polymer was extruded at 100 • C and allowed a single pneumatic extrusion without any other excipients (P1 in Table 2). However, when the PEO was mixed with 5% OLZ (F1 in Table 3), the printing temperature of ODF was approximately 170 • C owing to the effect of OLZ with a high melting point [40]. A high printing temperature was not appropriate because the loaded material burned quickly before printing.…”
Section: Optimization Of Polymeric Carrier Composition For Odf Printingmentioning
confidence: 99%
“…The PEO single polymer was extruded at 100 • C and allowed a single pneumatic extrusion without any other excipients (P1 in Table 2). However, when the PEO was mixed with 5% OLZ (F1 in Table 3), the printing temperature of ODF was approximately 170 • C owing to the effect of OLZ with a high melting point [40]. A high printing temperature was not appropriate because the loaded material burned quickly before printing.…”
Section: Optimization Of Polymeric Carrier Composition For Odf Printingmentioning
confidence: 99%
“…Due to the potential ability of the nanosystems to load pharmacologically active molecules, olanzapine [32] was selected as a model drug.…”
Section: Olanzapine Loading and Releasementioning
confidence: 99%
“…However, OL exhibits very slight solubility in water and suffers from extensive first pass metabolism and, therefore, possesses low bioavailability (40%) after oral administration (Sood et al, 2013). Numerous trials were reported in the literature for improving bioavailability of OL using solid lipid nanoparticles or through formation of solid dispersions with various polymeric carriers (Krishnamoorthy et al, 2009;Harde et al, 2011;Cavallari et al, 2013;Sood et al, 2013).…”
Section: Introductionmentioning
confidence: 99%